Sustaining Microfinancing Growth in Islamic Banking: Empirical Analysis of Internal Banking Determinants in Indonesia - Rachmah Nur Lativa; Jeni Susyanti; Abdullah Syakur Novianto (International Journal of Islamic Business and Economics (IJIBEC), 2026)
This study aims to analyze determinant of internal banking variables namely margin rate, Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) on the acceleration of microfinancing growth at Islamic commercial banks in Indonesia. Through a quantitative approach using multiple linear regression, this study examines the Financial Services Authority’s (OJK) monthly statistical reports from July 2022 - June 2025. The research findings reveal that the margin rate is a major determinant that significantly negatively affects financing growth, while CAR and NPF are not major determining factors during the observation period, the Financial Intermediation Theory explains that the success of the banking intermediation function is not only determined by capital adequacy but is also influenced by the level of trust. At the same time, these three variables significantly contribute to fluctuations in fund disbursement. Based on the stakeholder theory perspective, the management of Islamic banks is a required to be able to balance profitability targets with the interest of MSMEs as strategic stakeholders. This finding highlights how important it is for Islamic bank management to match their profit goals with what the market can handle to keep their services stable and accessible for everyone and a competitive margin rate policy.